Open‐source framework for power system transmission and distribution dynamics co‐simulation. Issue 12 (7th August 2017) - Huang, Renke; Fan, Rui; Daily, Jeff; Fisher, Andrew; Fuller, Jason
Abstract : The promise of the smart grid entails more interactions between the transmission and distribution networks, and there is an immediate need for tools to provide the comprehensive modelling and simulation required to integrate operations at both transmission and distribution levels. Existing electromagnetic transient simulators can perform simulations with integration of transmission and distribution systems, but the computational burden is high for large‐scale system analysis. For transient stability analysis, currently there are only separate tools for simulating transient dynamics of the transmission and distribution systems. In this study, the authors introduce an open‐source co‐simulation framework 'framework for network co‐simulation' (FNCS), together with the decoupled simulation approach that links existing transmission and distribution dynamic simulators through FNCS. FNCS is a middleware interface and framework that manages the interaction and synchronisation of the transmission and distribution simulators. Preliminary testing results show the validity and capability of the proposed open‐source co‐simulation framework and the decoupled co‐simulation methodology.